Variation of Cervical Cytology by Pap Smear and its Correlation with Cervical Biopsy in Patients Attending Birat Medical College Teaching Hospital, Morang, Nepal - Sinha, Amrita; Kafle, Santosh Upadhyaya; Singh, Mrinalini; Kafle, Neeta (Birat Journal of Health Sciences, 2021)
Introduction: Carcinoma cervix is the second most common cause of death in women worldwide and the most common cause in developing countries. Cervical papsmear is a simple, safe, noninvasive, outdoor and low cost effective screening method for detection of cervical lesion but has limitations and needs confirmation by histopathology. Cervical biopsy is a gold standard but invasive technique. Objectives: The main objective of this study is to find the changes of cervical cytology by pap smear and to correlate the changes observed in cervical cytology with cervical biopsy. Methodology: This is a hospital based prospective cross sectional study carried out from September 15, 2020  to May 31, 2021 in Birat Medical College where all pap smears received in the Department of Pathology were included in the study. The cases who had undergone both Pap smear and cervical biopsy were compared. The correlation was then done regarding cytological and histological diagnosis.Results: In this study, total 550 pap smears were performed and out of them 30 patients were advised for cervical biopsy. Majority of patients were in the age group of 31-40 (38.5%) years.  The Pap smear findings revealed 93.4% as negative for intraepithelial lesion or malignancy (NILM) and 6.5% as epithelial cell abnormality (ECA). ECA comprised atypical squamous cells of undetermined significance (ASCUS) with 3.6%, low-grade squamous intraepithelial lesion with 1.6%, and high-grade squamous intraepithelial lesion with 0.9%. There were 2 cases (0.4%) of malignancy. Sensitivity, specificity and positive predictive value of Pap smear were 90.9%, 89.5%, and 83.3%, respectively.Conclusion: Pap smear is a cost effective screening method for early detection of premalignant and malignant cervical lesions. However, biopsy is considered to be the gold standard for the confirmation of abnormalities detected in cervical smear provided that it is taken from the representative areas.